Nondestructive Evaluation of Masonry Materials used in Historic Philippine Structures - Mathew Harvey T. Peralta (IPTEK Journal of Proceedings Series, 2017)
Due to numerous tectonic activities in the Philippines, many old heritage and culturally important structures are in risk of sustaining damage. Unlike their modern counterparts, these structures are mostly made of adobe, clay, lime stones, bricks, blocks, rocks, and the like. These materials are mostly inhomogeneous and contain cracks of variable sizes, especially those with age, as are those used in Philippine structures. Since most of these structures are of cultural significance to the country, their preservation must be given importance. Their preservation would start in an evaluation of the structure in a way that would not damage the structure. As a method of evaluation of these structures, this research aimed to develop a correlation between mechanical properties of materials such as Young's modulus of elasticity and uniaxial compressive strength which are usually determined using destructive tests, and nondestructive parameters, such as ultrasonic pulse velocity and wave attenuation. This method would allow future evaluation of masonry structures in a nondestructive way which would in turn, preserve their historical and cultural worth. Ultrasonic testing was conducted to determine different wave characteristics of different masonry materials commonly used in old Philippine structures. These characteristics were then correlated with material properties obtained from destructive tests of the samples. The correlations obtained between the destructive and non-destructive parameters gave high values of coefficient of determination, resulting in a viable basis for modeling.